Features of method of medical physical culture at insufficiency of aortic valve - S.A. Kalmykov (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The basic approaches are considered to application of facilities of medical physical education at aortic insufficiency on the stages of physical rehabilitation. An analysis is conducted more than 20 literary sources. The mechanisms of medical action of physical exercises are specified - restorative influence, forming of temporal indemnifications, trophic action, normalization of the broken functions. It is set that task, forms, facilities, the methods of medical physical culture depend on the degree of weight of disease, degree of cardio-vascular insufficiency and stage of physical rehabilitation. Engaged in a medical physical culture conducted in form morning hygienical gymnastics, medical gymnastics, independent employments, dosed walks, walking on steps, mobile and sporting games. It is marked that sparing training and training the motive modes are instrumental in the gradual training of the cardio-vascular system. Recommended the dosed walking to lead to a to 5-8 km on the sparing training and to 8-12 km on training modes.